Indonesian mathematics teachers’ views on distance learning barriers during the early Covid-19 pandemic - Hongki Julie; Veronika Fitri Rianasari; Maria Suci Apriani (JRAMathEdu (Journal of Research and Advances in Mathematics Education), 2022)
The aim of this paper is to describe the views of mathematics teachers in Indonesia on the distance learning barriers during the early Covid-19 pandemic. Specifically, this paper investigates the barriers that teachers view as significant in distance learning and efforts taken to overcome the barriers during the early Covid-19 pandemic. This study employed a descriptive research design involving 415 mathematics teachers by snowball sampling to fill out an online questionnaire. This study shows that barriers related to pedagogical dimensions were perceived as significant in distance learning during the early Covid-19 pandemic. Moreover, this study reveals that most of the teachers did some efforts that can be done by the teachers themselves to overcome the barriers. Based on the findings, we argue that it is important to support teachers’ pedagogical competencies to conduct distance learning in order to face this current pandemic or any future crises that may potentially disrupt face-to-face learning.